Pemanfaatan Komoditas Kayu sebagai Kerajinan Desa Semoyo - Binarti, Floriberta (Jurnal Atma Inovasia, 2023)
Timber is a potential commodity that is mostly found in Semoyo Village. This potential needs to be developed and managed properly by the local community, so that it can improve the community's economy. For this reason, the author discusses the potential and processing of wood commodities in this journal. This wood commodity will be processed into a craft product in the form of wood decorations, household utensils, and woven crafts from wood fibers. The utilization of this wood commodity is carried out so that the wood products in Semoyo Village can be processed properly and provide income for the local community.